Les possibilités d’une île : escale chez Marcu Biancarelli, Michel Houellebecq et Angelo Rinaldi
Placed under the sign of paradox, the island space, singular, different, apart, remains a territory that arouses many reactions and presents itself as the epicentre of the imaginary. At each auctorial vision there is an apprehension of the island. The Corsica of Murtoriu: Ballad of the Innocent becomes a temporary space for a protagonist who thinks more and more of a departure, and who gets tired of the self-centred character of his contemporaries. With La Possibilité d’une île, Michel Houellebecq emphasizes the liberating dimension of the island, similar, at first, to a regained Paradise on Earth where the contagion of immortality is no longer a myth. But post-human utopia becomes dystopia. Finally, La Maison des Atlantes by Angelo Rinaldi depicts a suffocating, toxic, static Corsica, depicting a sterile prison island. These three stories pave the way for intercultural dialogue on the geocultural, geoenvironmental and geohistoric issues of island society.